Testing The Effect of Islamic Financial Inclusion, Infrastructural Quality on Economic Growth in Nigeria: New Insight From Bootstrap and Non-Linear ARDL - Sani Ibrahim, Saifullahi; Sanusi, Hussaina (IAIN Kudus, 2022)
Inclusive growth can hardly be achieved without improvement in the inclusive finance that would enable the vulnerable households to become key economic players. While efforts are now shifted towards the Islamic financial inclusion based on the realization of weakness of traditional financial inclusivity, the impact of Islamic financial inclusion particularly, its pathways of bridging infrastructural gaps and growth drive have been partially explored. This study examines the effect of Islamic financial inclusion, infrastructural quality on economic growth in Nigeria. The study uses monthly data covering from 2017 until 2020 which was analyzed via a newly developed Bootstrap Autoregressive Distributive Lag. The results reveal a number of findings. First, the result of bootstrap autoregressive distributed lag demonstrates that there is strong co-movement between economic growth, Islamic financial inclusion, Sukuk and infrastructural quality. This finding points to the existence of a strong positive relationship between Islamic financial inclusion, infrastructural quality and economic growth in Nigeria. Second, results from nonlinear models have revealed that Islamic financial inclusion and Sukuk have asymmetric effects on economic growth. This asymmetric pattern reinforces the claim that Islamic financial inclusion can play a dedicated role in ameliorating economic downturn. Third, the results of nonlinear causality reveal strong bidirectional causality Islamic financial inclusion, economic growth and Sukuk. In this sense, inclusive Islamic finance could play a dedicated role to help countries in overcoming economic recession.